Cancers Among US Organ Donors: A Comparison of Transplant and Cancer Registry Diagnoses. Issue 6 (8th April 2014) - Engels, E. A.; Castenson, D.; Pfeiffer, R. M.; Kahn, A.; Pawlish, K.; Goodman, M. T.; Nalesnik, M. A.; Israni, A. K.; Snyder, J.; Kasiske, B.
<x xml:space="preserve">Abstract</x> Transmission of cancer is a life‐threatening complication of transplantation. Monitoring transplantation practice requires complete recording of donor cancers. The US Scientific Registry of Transplant Recipients (SRTR) captures cancers in deceased donors (beginning in 1994) and living donors (2004). We linked the SRTR (52 599 donors, 110 762 transplants) with state cancer registries. Cancer registries identified cancers in 519 donors: 373 deceased donors (0.9%) and 146 living donors (1.2%). Among deceased donors, 50.7% of cancers were brain tumors. Among living donors, 54.0% were diagnosed after donation; most were cancers common in the general population (e.g. breast, prostate). There were 1063 deceased donors with cancer diagnosed in the SRTR or cancer registry, and the SRTR lacked a cancer diagnosis for 107 (10.1%) of these. There were 103 living donors with cancer before or at donation, diagnosed in the SRTR or cancer registry, and the SRTR did not have a cancer diagnosis for 43 (41.7%) of these. The SRTR does not record cancers after donation in living donors and so missed 81 cancers documented in cancer registries. In conclusion, donor cancers are uncommon, but lack of documentation of some cases highlights a need for improved ascertainment and reporting by organ procurement organizations and transplant programs.